'Judgemental category' is the major concept in ntozake shange's “For colored girls who have considered suicide/when the rainbow is enuf” - Alsanafi, Ismael Hasan; Mohd Noor, Siti Noor Fazelah; Abdul Kadir, Zulida (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This paper aims to explore the frequencies of using the Attitudinal resources in Shange‟s Postmodern American drama “For Colored Girls Who Have Considered Suicide/When the Rainbow is Enuf”. The purpose of that investigation is to make a comparative analysis among all three types of Attitude categories which are: Appreciation, Judgment, and Affect. In order to accomplish the role of being the spokesperson of black American women in the United States of America by delivering the real agony and oppression that those people faced because of their class, gender, and race. The playwright has presented and cantered on seven black women who encountered some form of neglect, harassment, and abuse; either emotionally, sexually, or physically. The analysing process has presented that the playwright had utilized many linguistic resources; „Judgement‟. This category is considered as one of the major Attitudinal systems in the discourse-semantic appraisal mode within Systemic Functional Linguistics (SFL) for interpersonal meanings. Judgement is connected with the evaluation of black women‟s characters as well as their behaviours in this literary text. This article intends to discover the reason behind the heavy use of that category compared with the other two types of Attitudinal system. The paper has adopted qualitative and quantitative methods to conduct the objectives of the Attitudinal resources in the selected data sets. This paper has concluded that in the Attitude category, Judgement turned to be the most presentation system comparing with the other Attitudinal types which are Affect and Appreciation. Moreover, within the scope of Judgement „Propriety‟ and „Tenacity‟ have exceeded other judgmental subtypes.